The Mediation of Buying interest to Shopping Lifestyle and Discount on Product Purchase Decision - Budiman Abdulah; Dewa Putu Yohanes Agata L. Sandopart; Denintha Dwi Hapsari (Universitas Bina Sarana Informatika, 2024)
This study aims to determine the effect of shopping lifestyle on buying interest, discounts on buying interest, buying interest in purchasing decisions, shopping lifestyle on purchasing decisions through buying interest and discounts on purchasing decisions through product buying interest in the Shopee Indonesia marketplace. This study uses a quantitative approach, with an unknown population and a sample of 200 respondents. The sampling technique uses a statistical calculation method, namely using the Hair et al formula. While the type of sample used is purposive sampling, the analysis method uses Structural Equation Modeling (SEM) SmartPLS software version 3.0. The results showed that shopping lifetsyle had a positive and significant effect on purchase intention, discount had a positive and significant effect on purchase intention, purchase intention had a positive and significant effect on purchasing decisions, shopping lifestyle had a positive and significant effect on purchasing decisions through purchase intention, discount had a positive and significant effect on purchasing decisions through purchase intention. The practical implications of this research are expected to help shopee companies to maintain sales promotions by providing discounts to their consumers, because shopping lifestyle and discounts have a significant influence on buying interest and purchasing decisions.